NLP-based AI robot for intelligent interaction - Dastagir, Golam; Hossain, Khaled Mushahed; Haque, Md Mahfujul; Gaffar, Raiyan Bin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.